2010
DOI: 10.1002/mren.201000034
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of Reactor Backmixing on RAFT Polymerization

Abstract: The effects of reactor backmixing on the outcome of RAFT polymerizations are examined. The kinetic model for the RAFT reaction is based on the first principle of mass balances and the method of moments. Two reactor models were applied for the simulation of backmixing, i.e., a PFTR with loop and multiple CSTRs in series. The models predict the behavior of monomer conversion, molecular weights, their distributions as well as the polydispersities for various chain types at different levels of backmixing. Both mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…[560] Kinetic simulation with a method of moments was used to model the effect of backmixing on the outcome of RAFT polymerization for a plug flow tubular reactor or for multiple continuous stirred tank reactors connected in series. [561] On-line monitoring of RAFT polymerization has been performed using ACOMP (automatic continuous online monitoring of polymerization reactions). [221,439,562] This technique [543] (EA) [543] (EA/MMA/Am) [543] 'R'-connected…”
Section: Toxicity Of Raft-synthesized Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…[560] Kinetic simulation with a method of moments was used to model the effect of backmixing on the outcome of RAFT polymerization for a plug flow tubular reactor or for multiple continuous stirred tank reactors connected in series. [561] On-line monitoring of RAFT polymerization has been performed using ACOMP (automatic continuous online monitoring of polymerization reactions). [221,439,562] This technique [543] (EA) [543] (EA/MMA/Am) [543] 'R'-connected…”
Section: Toxicity Of Raft-synthesized Polymersmentioning
confidence: 99%
“…Kinetic simulation was then used to predict residence time distributions and the effect of backmixing on the outcome of the process. [561,567] The effect of backmixing is to produce a higher dispersity and a lower average chain length than that expected based on reagent concentrations and conversion, thus it becomes important to exclude reactor backmixing as much as is possible. [561] Methods have also been developed to allow prediction of the monomer sequence distribution for such reactors.…”
Section: Raft In Continuous Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] RAFT agents such as dithioesters (1, Z= aryl or alkyl, e.g., [3][4][5][6] or trithiocarbonates (1, Z= alkylthio, e.g., 7-12) are suitable for controlling the polymerization of more activated monomers (MAMs; e.g., methyl methacrylate (MMA), styrene (St), methyl acrylate (MA), acrylamide (AM), and acrylonitrile (AN)) but inhibit or retard polymerizations of less activated monomers (LAMs, e.g., vinyl acetate (VAc), N-vinylpyrrolidone (NVP), and N-vinylcarbazole (NVC). RAFT agents such as xanthates (1, Z= alkoxy, e.g., 13,14) and N,N-dialkyl-or N-alkyl-N-aryl dithiocarbamates (1, Z= N,N-dialkylamino or N-alkyl-N-arylamino, e.g., 15,16) can be suitable for controlling polymerizations of LAMs but are ineffective with MAMs. The dithiocarbamate 16 is switchable such that, in neutral form, it controls the polymerizations of LAMs but, in its protonated form (17), provides effective control over the polymerization of MAMs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been theoretically shown that any level of reactor backmixing will broaden the molecular weight distribution in a CRP system . Zhu and coworkers have simulated the effects of reactor backmixing on the kinetics of RAFT polymerization in a continuous tubular reactor with recycle loop and in a series of CSTRs, demonstrating that backmixing causes a decrease in average chain length and increase in polydispersity of the molecular weight distribution. Russum et al have also observed a similar effect in an experimental study of nonideal plug flow behavior for RAFT miniemulsion polymerization in a tubular reactor.…”
Section: Future Challengesmentioning
confidence: 99%